Imperial Cities in the Tsarist, the Habsburg, and the Ottoman Empires - Hofmeister, Ulrich; Riedler, Florian (Routledge Advances in Urban History, 2024)
This book explores the various ways imperial rule constituted and shaped the cities of Eastern Europe until World War I in the Tsarist, Habsburg, and Ottoman empires. In these three empires, the cities served as hubs of imperial rule: their institutions and infrastructures enabled the diffusion of power within the empires while they also served as the stages where the empire was displayed in monumental architecture and public rituals. To this day, many cities possess a distinctively imperial legacy in the form of material remnants, groups of inhabitants, or memories that shape the perceptions of in- and outsiders. The contributions to this volume address in detail the imperial entanglements of a dozen cities from a long-term perspective reaching back to the eighteenth century. They analyze the imperial capitals as well as smaller cities in the periphery. All of them are ""imperial cities"" in the sense that they possess traces of imperial rule. By comparing the three empires of Eastern Europe this volume seeks to establish commonalities in this particular geography and highlight trans-imperial exchanges and entanglements. This volume is essential reading to students and scholars alike interested in imperial and colonial history, urban history, and European history.